PhXA34--a prostaglandin F2 alpha analogue. Effect on intraocular pressure in patients with ocular hypertension. - Villumsen, J. (1992)
PhXA34, a prostaglandin analogue, was given topically to 40 patients with untreated ocular hypertension in a double masked randomised study. One single dose of 0.3, 1, 3, 10 micrograms, or placebo (vehicle) was given to one eye of each patient. A dose related IOP reduction ranging from 11 to 35% was observed with a maximal effect with 3 and 10 micrograms PhXA34. No hyperaemia was seen except after 10 micrograms PhXA34, where a mild to moderate hyperaemia was seen from 8 hours with a duration of up to 24 hours. Mild foreign body sensation in the PhXA34-treated eye was noted by three patients. No cells or flare were seen.